EFEKTIVITAS PENERAPAN GELANG KAKI ELEKTRONIK SEBAGAI ALAT PENGAWASAN TAHANAN KOTA PADA KEJAKSAAN NEGERI SIDOARJO - Hesekiel Renhad Simanungkalit; hesekiel@student.undiksha.ac.id; Putu Riski Ananda Kusuma, S.H., M.H; Ario Dewanto, S.H., M.H (Jurnal Ilmu Hukum Sui Generis, 2026)
The use of electronic monitoring devices (EMDs) or electronic ankle bracelets as a tool for supervising detainees under city custody is part of efforts to modernize Indonesia’s criminal justice system in order to address the problem of overcrowding in state detention centers (rutan) and correctional institutions (lapas). This study aims to analyze the effectiveness of implementing electronic ankle monitors as a tool for supervising pretrial detainees at the Sidoarjo District Attorney’s Office and to identify the challenges encountered in their implementation. The method used is empirical legal research with a descriptive qualitative approach. Primary data were obtained through direct observation and in-depth interviews with the Head of Intelligence Subdivision I at the Sidoarjo District Attorney’s Office, while secondary data were sourced from relevant laws and regulations and official documents. The research findings indicate that the APE system has been implemented at the Sidoarjo District Attorney’s Office since 2025 in accordance with the Attorney General of the Republic of Indonesia’s Guideline No. 4 of 2023, with a total of 4 cases as of June 2026. Supervision is carried out in multiple layers through a real-time GPS monitoring system integrated with institutional oversight by the Intelligence Division, including the deployment of the TABUR Team to address violations in the field. Mechanisms involving monetary or personal guarantees further reinforce the defendants’ compliance. Challenges identified include violations of designated zones, defendants forcibly removing the devices, and delays in implementation at the work unit level. This study concludes that the APE is generally effective as a more modern and measurable instrument for supervising defendants under city detention compared to conventional mechanisms; however, it requires strengthening in terms of defendant compliance and broader, more equitable implementation across all district attorney’s offices.